THE EFFECT OF THE STUDENT TEAM-ACHIEVMENT DIVISION TYPE COOPERATIVE LEARNING MODEL ON STUDENTS' CRITICAL THINKING SKILLS - Sabrina, Eva; Hasmidyani, Dwi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Improving critical thinking skills is important because it helps students analyze information, make accurate decisions, solve problems logically, and avoid accepting information blindly. This study aims to prove the influence of the student team achievement divisions (STAD) learning model on students’ critical thinking skills in the entrepreneurship subject for 11th-grade students at SMK YP Gajah Mada Palembang. The method used in this research is an experimental method. The target population consists of 125 11th-grade students at SMK YP Gajah Mada Palembang, and the sampling technique employed was cluster random sampling, resulting in class XI.7 being selected as the experimental class. Data collection in this study utilized a test instrument, while data analysis techniques included test result analysis and observation. The prerequisite test used was the Chi-Square test for normality, and the hypothesis testing employed the Paired Sample t-test. The t-test results showed a of 18.74 and a value of 1.699, indicating that Ha is accepted and Ho is rejected, which means there is a proven influence of the STAD learning model on students’ critical thinking skills in entrepreneurship. Based on this research, it is expected that students will better understand and retain their learning outcomes, and that learning improvements will continue to be encouraged to further enhance student achievement through active engagement.